Four-Arm Grating Couplers for Wavefront Sensing Applications - Parent, Alexander (My University, 2023)
Atmospheric turbulence in free space optical satellite downlinks negatively impacts link availability and bit error rate. These effects can be mitigated using a compensation system capable of measuring the incoming wavefront distortion and applying a suitable correction to the received signal. The traditional solution based on adaptive optics and the Shack-Hartmann wavefront sensor has limitations in bandwidth, system complexity, size, weight, and power consumption. Signal correction can also be accomplished using a novel single-chip silicon photonic solution. This work introduces a four-arm grating coupler structure acting as a wavefront sensing element that emulates the performance of the Shack-Hartmann wavefront sensor by giving local tip and tilt estimation. FDTD simulations and measurements have confirmed the presence of a monotonic relationship between incident angle, polarization, and coupler output which can be converted to phase estimation through a reconstruction algorithm. An array of four-arm couplers on a silicon photonic chip provides enough sampling to fully reconstruct the wavefront, providing benefits over traditional solutions such as higher bandwidth, reduced size and weight, and reduced cost. Scaling up the results of this work to a full device could provide a solution for free space optical satellite to ground links in remote and rural communities across Canada and around the world.
Keywords: Optical Communications; Silicon Photonics